RESEARCH PARADIGMS AND METHODS - Donna Boedi Maritasari; Dina Fitri Sulastri; Jumiarti Septiani; Arya Anggara (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Research paradigms and research methods are two fundamental components that determine the quality, consistency, and credibility of scientific research. However, there are still misunderstandings regarding the relationship between research paradigms and research methods, particularly in determining the approach that best suits the research objectives. This study aims to analyze the concept of research paradigms and their relationship to the selection of research methods. The study employs a qualitative approach using library research through the analysis of various relevant scientific sources, including books, journal articles, and conference proceedings. Data were analyzed using content analysis to identify and synthesize various concepts related to research paradigms and methods. The results indicate that research paradigms—such as positivism, post-positivism, interpretivism, constructivism, pragmatism, and the critical paradigm—possess distinct characteristics that influence the selection of research methods. Furthermore, the pragmatist paradigm serves as the dominant foundation for the use of mixed methods. This study makes a theoretical contribution by clarifying the relationship between research paradigms and research methods and serves as a practical reference for researchers in determining the appropriate research approach.